Implementasi Kebijakan Pengelolaan Pedagang Kaki Lima Di Kabupaten Bojonegoro - Supriyanto, Andik; Priyanto (Soetomo Magister Ilmu Administrasi, 2023)
Implementation of street vendor management policies in Bojonegoro district. The aim of this research is to describe and analyze the data: 1) to find out what the management policy for street vendors is in Bojonegoro Regency and 2) to find out the inhibiting and supporting factors for the Management Policy for Street Vendors in Bojonegoro Regency. Then the second research focus is the steps taken by the Bojonegoro Regency Government in handling street vendors (PKL) and efforts to ensure that street vendors participate in development in Bojonegoro Regency are efforts that can be made to improve the business of street vendors so that they can increase profits. which can increase the per capita income of Bojonegoro Regency. The indicators: expansion of business scale and expansion of business scope. The results of this research are that even though the Bojonegoro Regency Government has given advice and outreach, there are still many street vendors who choose to continue selling in the Bojonegoro Square area and carry out resistance. held a demonstration in front of the Bojonegoro Regency Government Building. The reason why street vendors are resisting this policy is because there are few buyers in the places provided by the government which makes their goods sell less and ultimately makes them determined to return to selling in the Bojonegoro Square area. Keyword: Policy Implementation, Street Vendors